Invention and Description of p-CuO /n-Si (200 oC) Heterojunction for Photodiode Applications - Ahmed N. Abd (Journal of Global Pharma Technology, 2019)
P-CuO /n-Si was prepared and studied with respect to Drop casting method  at  200°C temperature, it was concluded that energy band gap of CuO films is (1.6)eV calculated from optical properties. AFM reveal that the generated CuO Films have ball-shape with perfect homogeneity, the measurements of the XRD revealed that the CuO were of cubic crystal structure, the responsively photo detector after deposited CuO showed an increase in response.Keywords: CuO, Structure properties, AFM, Optical properties, Solar cell.